Mammalian evolution, diversity and systematics - Zachos, Frank E., 1974- (Handbuch der Zoologie., 2018)
The Handbook of Zoology provides an in-depth treatment of the entire animal kingdom covering both invertebrates and vertebrates. It publishes comprehensive overviews on animal systematics and morphology and covers extensively further aspects like physiology, behavior, ecology and applied zoological research.